2018
DOI: 10.1680/jmacr.17.00079
|View full text |Cite
|
Sign up to set email alerts
|

Calcium chloride acceleration in ordinary Portland cement

Abstract: Early-age hydration of ordinary Portland cement is now acknowledged to originate from nucleation and crystal growth of calcium–silicate–hydrates. The acceleration mechanism of water-soluble inorganic substances, such as calcium chloride, is still unclear. In the present study, the acceleration mechanism was approached in two independent ways. First, the acceleration effect of filler materials (limestone and quartz powder) and calcium chloride (CaCl2) were studied experimentally with a conduction calorimeter. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…These results are in agreement with the data reported by Liu et al [ 42 ], where it was shown that after one year of accelerated carbonation exposure (20% CO 2 , 70% RH, 20 °C), the carbonation depth was reduced by approximately 20–50% for concrete samples containing admixed chlorides (0.076% by concrete weight, or ≈0.5% by cement weight), compared to chloride-free samples. According to literature in References [ 42 , 45 , 46 , 47 , 48 ], it would thus be generally expected that a higher amount of admixed chlorides translates into a higher carbonation resistance. A reason for this may be that admixed chlorides accelerate cement hydration [ 45 , 46 ] and may lead to a denser pore structure of the cement paste [ 42 , 47 ], which generally increases the carbonation resistance [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with the data reported by Liu et al [ 42 ], where it was shown that after one year of accelerated carbonation exposure (20% CO 2 , 70% RH, 20 °C), the carbonation depth was reduced by approximately 20–50% for concrete samples containing admixed chlorides (0.076% by concrete weight, or ≈0.5% by cement weight), compared to chloride-free samples. According to literature in References [ 42 , 45 , 46 , 47 , 48 ], it would thus be generally expected that a higher amount of admixed chlorides translates into a higher carbonation resistance. A reason for this may be that admixed chlorides accelerate cement hydration [ 45 , 46 ] and may lead to a denser pore structure of the cement paste [ 42 , 47 ], which generally increases the carbonation resistance [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to literature in References [ 42 , 45 , 46 , 47 , 48 ], it would thus be generally expected that a higher amount of admixed chlorides translates into a higher carbonation resistance. A reason for this may be that admixed chlorides accelerate cement hydration [ 45 , 46 ] and may lead to a denser pore structure of the cement paste [ 42 , 47 ], which generally increases the carbonation resistance [ 42 ]. Another aspect to consider, however, is that the presence of chlorides in concrete promotes moisture retention, retarding the drying process [ 48 ], which decelerates the carbonation process under some exposure conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Other cations of a similar size and charge, that are is a similar charge density, would also show an accelerated reaction mechanism [107]. Thus, the effectiveness of cations as a chemical accelerator is as follows [108,109]: Ca 2+ > Sr 2+ > Ba 2+ > Li + > K + > Na + ≈ Cs + > Rb + The counter ion which would maintain the electroneutrality of the sample, should not bind to either CSH or alite during the hydration process, by replacing the silicates.…”
Section: Acceleratormentioning
confidence: 99%
“…However, at Days 28 and 90, the cement samples gained the highest compressive strength at a CaCl 2 concentration of 1.5%, and the compressive strength decreased as the concentration of CaCl 2 increased to 2%. The increase in compressive strength of the OPC with the addition of CaCl 2 is discussed thoroughly by another study [15] through a calorimetric study and thermodynamic modelling, and it was revealed that the CaCl 2 resulted in a higher supersaturation of C-S-H, which reduced the free energy barrier and consequently enhanced the nuclei formation on the cement surface.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of studies that have investigated the influence of CaCl 2 in cement under exposure to HPHT conditions. Previous studies were conducted at ambient conditions, which is at atmospheric pressure and temperature and hence different to the downhole HPHT conditions [15][16][17]. Furthermore, previous studies predominantly focused on concrete, where the composition of concrete is different to well cement [17,18].…”
Section: Introductionmentioning
confidence: 99%